1996
DOI: 10.1152/jappl.1996.81.2.611
|View full text |Cite
|
Sign up to set email alerts
|

Breathing and brain blood flow during sleep in patients with chronic mountain sickness

Abstract: Chronic mountain sickness (CMS) patients have lower arterial O2 saturation (SaO2) during sleep compared with healthy high-altitude residents, but whether nocturnal arterial O2 content (CaO2) and brain O2 delivery are reduced is unknown. We measured SaO2, CaO2, sleep-disordered breathing (SDB), and internal carotid artery flow velocity in 8 CMS patients, 8 age-matched healthy CMS controls, 11 healthy younger-aged Han, and 11 healthy younger-aged Tibetan male residents of Lhasa, Tibet (3,658 m). CMS patients spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 0 publications
5
35
1
Order By: Relevance
“…1), and may thus explain at least in part why, even in the absence of major respiratory disorders some subjects develop polycythaemia, while others do not, despite intergroup small differences in Sa,O 2 . At an altitute of 3,100 m (Leadville, Colorado) and at 3,658 m (Lhasa), it has been found that nocturnal hypoxaemia in polycythaemic subjects is more marked compared with the EE group (although polycythaemia is less severe at lower altitude) [6,7]. One possible explanation is that there may be differences between ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), and may thus explain at least in part why, even in the absence of major respiratory disorders some subjects develop polycythaemia, while others do not, despite intergroup small differences in Sa,O 2 . At an altitute of 3,100 m (Leadville, Colorado) and at 3,658 m (Lhasa), it has been found that nocturnal hypoxaemia in polycythaemic subjects is more marked compared with the EE group (although polycythaemia is less severe at lower altitude) [6,7]. One possible explanation is that there may be differences between ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is based on the observation that hypoventilation is a physiological feature of the sleep state at sea-level as well [5]. In addition, substantial nocturnal hypoxaemia has been reported in highlanders at 3,100 m and 3,658 m [6,7] and sleep-disordered breathing (SDB) is a common finding in lowlanders ascending to high altitude [8][9][10]. COOTE and co-workers [11,12] were the first to perform sleep studies in healthy Andean natives above 4,000 m and to determine the presence of nocturnal periodic breathing associated with a moderate fall in arterial oxygen saturation (Sa,O 2 ).…”
mentioning
confidence: 99%
“…Not only do Peruvians hyperventilate in response to high altitude hypoxia, but they are also at increased risk of periodic breathing and apnoea, particularly during sleep, 26,27 which may be attributable to their reduced cerebral reactivity to The cerebral reactivity to hypocapnia during hypoxia was greater in Ethiopians than Peruvians when tested at high altitude ( †PϽ0.05). After descent to low altitude, responses were significantly reduced in all 3 groups (*PϽ0.05; **PϽ0.01).…”
Section: Respiratory Adaptationsmentioning
confidence: 99%
“…Central sleep apnoea is linked to both chronic hypoxia 27 and stroke, 30 and patients with recurrent transient ischemic attacks have reduced cerebral CO 2 reactivity. 31 In addition, NO is implicated in cerebrovascular disease and stroke at sea level 32 and likely mediates altered cerebral responses to hypoxia and hypocapnia.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Specifically, ambient hypoxia and hypoxemia destabilize respiratory patterns and play a major role in the pathogenesis of periodic breathing. In several small case series, investigators have documented a high prevalence of central and obstructive sleep apnea and nocturnal hypoxemia in highlanders (Kryger et al, 1978;Lahiri et al, 1983b;Coote et al, 1992;Normand et al, 1992;Sun et al, 1996;Arai et al, 2002;Pływaczewski et al, 2003;Spicuzza et al, 2004;Julian et al, 2013). Large uncontrolled surveys in clinical patients have also reported high rates of periodic apneic events (Bazurto et al, 2014).…”
mentioning
confidence: 99%